2022
DOI: 10.24815/siele.v9i1.21089
|View full text |Cite
|
Sign up to set email alerts
|

ICT platforms for Indonesian EFL students viewed from gender during the COVID-19 pandemic

Abstract: The aims of this study are to find out (1) ICT (Information and Communications Technology) platform used by male and female students from Islamic universities in Indonesia, (2) their perception of using ICT, and (3) their barriers to using ICT in English language learning during the COVID-19 pandemic. The data was collected from an online questionnaire (Google Form) from students majoring in English from seven Islamic universities in Indonesia. There were 30 male students and 30 female students from every univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…The results also showed a significant difference in respondents' sex on the attitude towards virtual learning Females had more difficulty using learning tools than did males (Apriani et al, 2022), consequently male students in the Philippines viewed virtual learning more favourably. According to Apriani et al (2022), males are more flexible and receptive to a virtual set-up in general; because females complain more on learning connection, resources, and technology skills, so are more likely to find virtual learning activities relevant.…”
Section: Perceived Level Of Opportunities Gained By Students During V...mentioning
confidence: 84%
“…The results also showed a significant difference in respondents' sex on the attitude towards virtual learning Females had more difficulty using learning tools than did males (Apriani et al, 2022), consequently male students in the Philippines viewed virtual learning more favourably. According to Apriani et al (2022), males are more flexible and receptive to a virtual set-up in general; because females complain more on learning connection, resources, and technology skills, so are more likely to find virtual learning activities relevant.…”
Section: Perceived Level Of Opportunities Gained By Students During V...mentioning
confidence: 84%
“…Chen et al [31] also reported that during the period of 2000 -2021, the documents of researches about the technology-enhanced language learning have been fluctuately cited. The number of citations to the documents will go up in the future because the studies about technology-based foreign language learning during COVID-19 are the trending topic in educational research [18], [47], [48].…”
Section: ) Publication and Citation Trend Analysismentioning
confidence: 99%
“…Hereinafter, there were several keywords interpreting foreign language studied in the documents related to technology-based foreign language learning during the COVID-19 pandemic such as "English for academic purpose", "English language", "EFL", and "English as a foreign language". It shows that English was the most familiar language studied as a research topic in the COVID-19 outbreak in which some researchers focused their topic on the English language [18], [47], [64], [65], although some other foreign languages were also studied as a research topic such as Chinese [14], Japanese [11], Russian [9], and Arabic [12]. In addition, there were some keywords interpreting measured skills or abilities in the foreign language learning such as "communication skills" and "digital literacy".…”
Section: ) Co-word Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in cognitive ability show that female verbal abilities are superior to men, men's visual-spatial abilities (spatial vision) are superior to women, and men's mathematical abilities are superior to women. Various motivational studies on gender disparities in foreign language learning have revealed that women are more inspired than boys to study foreign languages (Apriani, et. al, 2022).…”
Section: Factors Influencing Self-directed Learningmentioning
confidence: 99%